Reputation management : the future of corporate communications and public relations - Langham, Tony (Company founder) (PRCA practice guides., 2019)
The book aims to give senior executives and communications professionals a guide to the importance of reputation (in terms of how positively or negatively an organisation is perceived by stakeholders such as employees, customers and members of the media), and inspire their thinking in managing reputation.